The Trans-Neptunian Automated Occultation Survey (TAOS II). Issue Volume 14:Issue S339(2018) (November 2017) - Lehner, M. J.; Wang, S-Y.; Reyes-Ruiz, M.; Zhang, Z-W.; Figueroa, L.; Huang, C-K.; Yen, W-L.; Alcock, C.; Alvarez Santana, F.; Castro-Chacón, J.; Chen, W-P.; Chu, Y-H.; et al.
Abstract: TAOS II is a next-generation occultation survey with the goal of measuring the size distribution of the small end of the Kuiper Belt (objects with diameters 0.5–30 km). Such objects have magnitudes r > 30, and are thus undetectable by direct imaging. The project will operate three telescopes at San Pedro Mártir Observatory in Baja California, México. Each telescope will be equipped with a custom-built camera comprised of a focal-plane array of CMOS imagers. The cameras will be capable of reading out image data from 10, 000 stars at a cadence of 20 Hz. The telescopes will monitor the same set of stars simultaneously to search for coincident occultation detections, thus minimising the false-positive rate. This talk described the project, and reported on the progress of the development of the survey infrastructure.